Somatic Mosaicism for Paternal Uniparental Disomy of 11p15.5 Region in Adrenal and Liver Tissues in a Newborn with Atypical Beckwith–Wiedemann Syndrome - Urzua, Abraham; Burattini, Sofia; Pinochet, Constanza; Benavides, Felipe; Repetto, Gabriela M. (Journal of Pediatric Genetics, 2019)
Beckwith–Wiedemann syndrome (BWS) is characterized by overgrowth and increased risk of embryonic tumors. It results from alterations in genes controlled by imprinting centers H19DMR (Imprinting Center [IC] 1) and KvDMR (IC2). Strategies for diagnostic confirmation include methylation analysis and CDKN1C sequencing. We present a newborn with placentomegaly, hyperinsulinism and adrenal cytomegaly, but no typical external features of BWS. The patient had normal genetic studies in blood. However, adrenal and liver tissues showed hypermethylation of IC1 and hypomethylation of IC2. Microsatellite analysis confirmed mosaic paternal uniparental disomy. This study demonstrates the importance of analyzing additional tissues to reduce underdiagnosis of somatic mosaicism in BWS.
Keywords: Beckwith–Wiedemann syndrome; hyperinsulinism; mosaicism; neonatal hypoglycemia; uniparental disomy